Real Exchange Rates and Fundamentals : A Cross-Country Perspective - Ricci, Luca (IMF Working Papers; Working Paper, 2008)
This paper employs newly constructed measures for productivity differentials, external imbalances, and commodity terms of trade to estimate a panel cointegrating relationship between real exchange rates and a set of fundamentals for a sample of 48 industrial countries and emerging markets. It finds evidence of a strong positive relation between the CPI-based real exchange rate and commodity terms of trade. The estimated impact of productivity growth differentials between traded and nontraded goods, while statistically significant, is small. Increases in net foreign assets and in government consumption tend to be associated with appreciating real exchange rates.